Efektivitas Pengelolaan Zakat di Baznas Kota Bekasi dengan Prinsip Transparansi dan Akuntabilitas - Joni Tesmanto; Riyanto Riyanto (Research and Strategic Studies Center (Pusat Riset dan Kajian Strategis) Fakultas Syariah IAI Nasional Laa Roiba, 2023)
The objectives to be achieved by the authors in this study are to determine the Effectiveness of Zakat Management Management at BAZNAS Bekasi City with the Principles of Transparency and Accountability. Then specifically, this research has goals and uses which are expected to be useful for the community at large and for employees of BAZNAS Bekasi City. This type of research is field research (Field Research). Field research is research with data obtained from direct research on activities in the research field. The data were collected by the researchers directly from the sources, namely the manager of BAZNAS Bekasi City, Muzaki (community) and Munfik. This research was conducted from November 2021 to February 2022. BAZNAS Bekasi City has implemented the principle of transparency for its employees, every year a meeting is held to find out what plans will be implemented. BAZNAS Bekasi City has an RKAT (Annual Budget Work Plan) in which this RKAT must be approved by the province. From the results of the discussion, it can be concluded that the implementation carried out by BAZNAS Bekasi City is accountable based on predetermined standards that have been planned. In its implementation, Bekasi City BAZNAS does not only work alone, but also cooperates with several parties, such as collaboration with Bulog (Logistics Affairs Agency), Villages, Urban Villages, and Schools to find out data on underprivileged or high achieving students. The management of BAZNAS Bekasi City should always implement policies that are in line with the ideals of zakat management, namely the welfare of the people, namely by prioritizing the allocation for productive zakat schemes. If there is a standard allocation per scheme for the zakat program set by BAZNAS Bekasi City, then there should be optimal monitoring of the realization of distribution so that the target and realization run in harmony. Keywords: Effectiveness, Zakat, Principle of Transparency, Accountability